Fraud as a Moderating Factor in the Relationship Between Good Corporate Governance and Firm Value: Evidence from Indonesian Banking - Firly Irhamni; Salsabila Nanda Aulia Tsani (JURNAL AKUNTANSI DAN MANAJEMEN, 2026)
This study examines the influence of profitability, dividend policy, and Good Corporate Governance (GCG) mechanisms on firm value in Indonesian commercial banks, with fraud tested as a potential moderating variable. Using a fixed effects panel regression model on 105 firm-year observations, the results confirm that board independence, audit committee, managerial ownership, dividend payout ratio (DPR), and return on assets (ROA) collectively exert a significant simultaneous effect on firm value (PBV). Individually, board independence and ROA positively and significantly influence firm value, while the audit committee shows a negative effect, and both managerial ownership and DPR are insignificant. Fraud, whether included directly or as a moderator, does not significantly alter these relationships. The findings highlight that profitability and board independence remain the dominant determinants of firm value in emerging-market banking, supporting agency, resource dependence, and signaling theories. The absence of a moderating effect from fraud suggests that governance structures in Indonesian banks remain relatively resilient despite variations in fraud exposure. These results provide theoretical insight into governance dynamics in developing economies and practical implications for policymakers and banking regulators to strengthen governance enforcement and profitability-driven value creation.